La poétique de la pierre dans l'œuvre de Thomas Hardy : du livre de pierre au livre de vie - Annie Escuret (Cahiers Victoriens et Edouardiens)
Stones are everywhere to be found in Hardy's works. His father worked as a stonemason and Hardy himself trained as an architect. The years that he spent in London moving churchyards for the railway and restoring churches made a painful impression on him. Back in Dorset, he was confronted with the Neolithic monuments of Stonehenge and other pagan monuments such as the tumuli on Egdon Heath and other landmarks. Hardy knew all about archaeology and all about the religious aspects of the past. In other words, through the plight of characters such as Eustacia, Tess or Jude, we are always reminded about past customs such as the bonfires on the hills which recall druidic and Saxon times. Tess's tragedy is summed up by a series of stones (including the pillar of stone « Cross-in-Hand » on which is carved a human hand) and the same applies to Jude's fate (with the milestone on which he carves his name). Most characters are alienated by their education and their tragedy comes from the fact that their own time never comes ! Tess feels « at home » only at the end, on the warm slab at Stonehenge, because the pagan tomb is the only place where she can find rest and sleep.In a word, Hardy uses stones to build up his own distinction between the figurative (which refers to the classical, mimetic aesthetic) and the figural (which refers to writing as play), between the Word made flesh (when the relation of meaning to the world is one of transcendence) and when the idea is never made carnally present at all (because a novel is first of all an event of writing). In La Parole muette (1998), Rancière insists on the paradoxes of literary representation as novels seem to indicate an embodied world that is forever awaiting embodiment, a liminal world which reminds us of Derrida's concept of the « spectral ». Rancière's works are helpful because they help us find a way out of the usual barren oppositions between mimetic aesthetics and the postmodern conceptions of representation as he shows us how literature manages to reorganize the relations between past and future communities and between words and things.